A retrospective case study of sunitinib treatment in three patients with Von Hippel-Lindau disease. Issue 9 (2nd September 2018) - Yuan, Gang; Liu, Qiuli; Tong, Dali; Liu, Gaolei; Yi, Yuting; Zhang, Jun; Zhang, Yao; Wang, Lin-ang; Wang, Luofu; Chen, Rongrong; Guan, Yanfang; Yi, Xin; et al.
Abstract: Von Hippel-Landau (VHL) disease is characterized by malignant and benign tumors in multiple organs. Sunitinib, a tyrosine kinase inhibitor, has been clinically available for treating sporadic patients with recurrent or unresectable and metastatic clear renal cell carcinomas (cRCCs) and metastatic lesions of the lung, but its effect on VHL disease-associated tumors remains poorly understood. This retrospective case series examined the effect of sunitinib on RCC, hemangioblastomas, pheochromocytomas, and pancreatic neuroendocrine tumors in patients with confirmed VHL. Of note, three patients with VHL disease who were treated with sunitinib were identified from a review of their medical records. The efficacy of sunitinib was evaluated by comparing computed tomography (CT) or magnetic resonance imaging (MRI) scans conducted before and after treatment. Adverse side effects associated with sunitinib were assessed and recorded. All three patients with VHL disease exhibited clinical improvement after treatment with sunitinib. Patient 1 exhibited a decrease in the size of both their pheochromocytoma and RCC after 19 months of sunitinib treatment. RCCs in Patients 2 and 3 exhibited stable response to sunitinib for approximately 1 and 6 years, respectively. All the patients reported tolerable side effects. Therefore sunitinib treatment was associated with either partial response or stable control of VHL-related RCCs, pheochromocytomas and pancreatic neuroendocrine tumor (NET) with acceptable side effects. Further evaluation of sunitinib in patients with VHL disease in larger prospective studies is warranted.